Systemic immune-inflammatory index predicts fragility fracture risk in postmenopausal anemic females with type 2 diabetes mellitus: evidence from a longitudinal cohort study - Dinggui Huang; Qi He; Jiangmei Pan; Zhenwei Zhai; Jingxia Sun; Qiu Wang; Wenxin Chu; Jianhao Huang; Jinming Yu; Xiaoqin Qiu; Wensheng Lu (BMC Endocrine Disorders)
Abstract Background Chronic low-grade inflammation is related to bone metabolism in patients with type 2 diabetes mellitus (T2DM). However, credible data indicating the relationship between inflammation and fragility fracture risk in postmenopausal anemic females with T2DM are sparse. The current study sought to investigate the relationships between the systemic immune-inflammatory index (SII) and fragility fracture events, as well as the future 10-year fragility fracture probability evaluated using the fracture risk assessment tool (FRAX) in postmenopausal females with T2DM. Methods According to the tertiles of SII, 423 postmenopausal females with T2DM were divided into three groups: low-level (≤ 381.32, n = 141), moderate-level (381.32–629.46, n = 141), and high-level (≥ 629.46, n = 141). All participants were followed up for 7 years with a median of 46.8 months (1651 person-years). The association between SII and fragility fracture risk was assessed. Results Of 423 subjects, 75 experienced a fragility fracture event. Spearman partial correlation analysis revealed that SII was negatively related to bone mineral density (BMD) and was positively associated with the future 10-year probability of major osteoporotic fracture (MOF) and hip fracture (HF). Restricted cubic spline (RCS) analysis revealed a positive correlation between SII and fragility fracture risk in an approximately inverted J-shaped dose–response pattern (P for overall < 0.0001). Multivariate Cox regression analysis demonstrated that patients with a high SII presented a greater risk of fragility fractures (P = 0.011). Stratified analysis revealed that fragility fractures in the high-level SII were predominantly associated with anemia with an increase of 4.15 times (P = 0.01). Kaplan‒Meier analysis indicated a greater cumulative incidence of fragility fractures in patients with a high SII (log-rank, all P = 0.0012). Receiver operating characteristic (ROC) analysis indicated an optimal SII cut-off value of 537.34, with an area under the curve (AUC) of 0.646, a sensitivity of 60%, and a specificity of 64.1% (P < 0.001). Conclusion The SII revealed a significant positive association with a real-world fragility fracture event and a future 10-year fragility fracture probability in postmenopausal females with T2DM, particularly evident in individuals with anemia. Therefore, monitoring the SII and hemoglobin in postmenopausal older women with T2DM is helpful in routine clinical practice to identify individuals at high risk for fragility fractures and to promptly execute appropriate fracture intervention procedures.